Rhombencephalitis acute caused by Listeria monocytogenes: a case report - Flores Palacios, Rodrigo (2022)
Rhombencephalitis is inflammation of the brainstem and cerebellum; one of the causes of this entity is Listeria monocytogenes, although it is an unusual presentation. The case is a 70-year-old woman with high blood pressure, obesity, bronchial asthma, and hypothyroidism. She began a 6-day clinical picture with nausea, vomiting, and headache, then dizziness and right lateropulsion were added, and a nuclear magnetic resonance was performed, diagnosing ischemic stroke in the medulla oblongata. She is hospitalized, she has a fever of 38.5 °C, compromised level of consciousness, and neck stiffness. Listeria monocytogenes infection was confirmed by CSF culture, she received meropenem, vancomycin, ampicillin, and dexamethasone, then the patient fully recovered on the fifth day of antibiotic treatment, without neurological sequela. The presence of posterior fossa symptoms on a CNS inflammatory background should lead to suspicion of rhombencephalitis due to Listeria; early antibiotic treatment limits neurological sequela.